Transcriptomic analysis identifies shared biological foundations between ischemic stroke and Alzheimer’s disease - Liu, Wenhao; Wan, Mengyao; Shi, Yinchao; Yang, Xin-Zhuang (Frontiers in Neuroscience, 2022)
AIM: Alzheimer’s disease (AD) and ischemic stroke (IS), two major neurological diseases, are suggested to be associated in clinical and pathophysiological levels. . Previous studies have provided some insights into the possible genetic mechanisms behind the correlation between AD and IS, but this issue is still not clear. We implemented transcriptomic analysis to detect common hub genes and pathways to help promote the understanding of this issue. METHODS: Four gene expression profiling datasets (GSE16561, GSE58294, GSE63060 and GSE63061) of peripheral whole blood, which contain 108 IS samples, 284 AD samples, and 238 matched controls, were employed to detect differentially expressed genes (DEGs) for AD and IS, which were further analyzed for shared biological pathways, candidate drugs, and transcription factors. Protein-protein interaction (PPI) network and drug-target interaction analysis were applied to identify hub genes and drug targets respectively. Result verification was done with other independent datasets (GSE37587, GSE46480 and GSE140829). . The difference in proportions of various immune cells in the peripheral blood of AD and IS patients were evaluated using CIBERSORT. RESULTS: We identified 74 DEGs and 18 biological processes with statistical significance shared by AD and IS, 9 of which were immune-related pathways. Five hub genes scored high in the topological analysis of the PPI network, and we also found eight drug target genes and candidate drugs which were associated with AD and IS. As for immunological changes, an increase in the proportion of M0 macrophages was found in the peripheral circulation of both AD and IS patients, and SOD1 expression was significantly correlated with this change. CONCLUSION: Collectively, the common DEGs and shared pathways found in this study suggest a potential shared etiology between AD and IS, behind which immune system, particularly the M0 macrophage elevation, might have important roles. . While, the shared hub genes, potential therapeutic gene targets and drugs reported in this study provide promising treatment strategies for AD and IS.